Implementation Of Values In Character Education Surah Al-Ahzab Verse 21 Perspective Of Tafsir Al-Misbah - Zakiyudin Fahmy; Ria Resti Fauziah (Journal of Social Science and Economics, 2023)
This research is a descriptive qualitative research. The research subjects were teachers and students of MI Miftahut Tholibin Gresik. Data collection methods used are observation, interviews, documentation. This study aims to determine the implementation of character values in Surah al Ahzab verse 21 according to the interpretation of al misbah at MI Miftahut Tholibin Gresik. what are the supporting and inhibiting factors of the implementation of character education values in surah al ahzab verse 21 according to the interpretation of al misbah at MI Miftahut Tholibin Gresik. The results of the study show: first, the values of character education in Surah al Ahzab verse 21 are the character of uswatun repertoire, the character of Sidiq, Amanah, Fathanah and Tabligh which are implemented into the method of habituation and punishment. in the form of habituation of exemplary done by teachers, habituation of fardhu prayers, habituation of three languages and habituation of clean and beautiful Fridays carried out by students and teachers. There are supporting factors in the form of cooperation from school residents, the cohesiveness of educators and community participation. Thus it can be concluded that MI Miftahut Tholibin Gresik implements the values of character education in Surah al Ahzab verse 21 according to the interpretation of al misbah well.